Integrating mindfulness and physical activity: a meta-analysis of mindful movement interventions for symptoms of anxiety and depression among university students - Xu, Xinjian; Abdullah, Borhannudin; Samsudin, Shamsulariffin; Tan, Yongneng (PeerJ Inc., 2025)
Background. University students are increasingly vulnerable to mental health problems, such as anxiety and depression, which have been associated with academic stress, job market uncertainty, and lifestyle-related factors such as physical inactivity and poor sleep habits. Mindful movement, defined as structured programs integrating mindful- ness practice with physical movement, offers a holistic approach to reducing anxiety and depression, though its effectiveness and specific intervention differences_such as duration, delivery mode, and behavior change techniques_remain underexplored. This study evaluated the effects of mindful movement interventions on anxiety and depression among university students. Methods. A systematic search of six databases up to August 2024 identified 19 randomized controlled trials involving a total of 1,697 participants. A random-effects model was employed to pool effect sizes; subgroup analyses were conducted to explore sources of heterogeneity, and sensitivity analyses were performed to test the robustness of the results. Results. The meta-analysis indicated that mindful movement interventions significantly reduced anxiety (standardized mean difference (SMD)D–0.42, 95% confidence interval (CI) [–0.52 to –0.31], p<0:0001, I2 D70%) and depression (Standardized Mean Difference (SMD) D –0.61, 95% CI [–1.01 to –0.20], p<0:0001, I2 D87%) compared to control groups. Subgroup analyses demonstrated no significant differences in effect sizes across different mindful movement types (yoga, tai chi, qigong). Meta- regression indicated that intervention type did not significantly explain heterogeneity (pD0:495). Publication bias was not observed in most subgroups, except for potential bias in the tai chi group due to limited studies. Conclusion. Mindful movement interventions are associated with enhanced mental health among university students, with no significant differences in the effects of yoga, tai chi, and qigong on reducing symptoms of anxiety and depression. It supports treating mindful movement as a unified approach to analyzing its impact on mental health. Residual heterogeneity highlights the need for further research on specific intervention elements and intervention and participant-related factors. PROS- PERO registration number (CRD42024569238).